Influence of Printing Orientation on the Mechanical, Surface, and Polymerization Properties of Two 3D-Printed Dental Resins - Vargas Koudriavtsev, Tatiana (2026)
This study aimed to evaluate the effect of printing orientation on the accuracy, flexural strength, surface roughness, and degree of conversion of two methacrylate-based resins commonly used in dental 3D printing. Rectangular specimens (64×10×3.3 mm) were designed according to ISO 20795-1:2013 standards and printed using an Asiga Max UV printer at three orientations (0°, 45°, and 90°) with two commercial resins: VeriGuide OS and VeriModel OS (Whip Mix). Dimensional accuracy was measured using a digital caliper, surface roughness by profilometry, and flexural strength through a three-point bending test. The degree of conversion (DC) was assessed using Attenuated Total Reflection Fourier Transform Infrared Spectroscopy (ATR-FTIR). Data were analyzed with one-way ANOVA and Tukey’s post hoc test (α=0.05). Printing orientation significantly influenced several properties of the tested resins (p≤0.05). Specimens printed at a 45° angle showed the highest dimensional accuracy in length, width, and thickness. Flexural strength increased as the printing orientation became more vertical, with significant differences between 0° and 90° for both resins. Surface roughness was highest at 45°, while smoother surfaces were observed at 0°. The mean DC values were approximately 40% for all groups, with statistically significant differences observed only for the VeriGuide resin, where specimens printed at 0° achieved higher conversion compared to 45° and 90° orientations. Specimens printed at 45° demonstrated superior dimensional accuracy and higher surface roughness, while vertical orientations enhanced flexural strength. None of the resins achieved complete polymerization.